Фінансово-правові аспекти розміжування змісту валютних обмежень та валютного контролю - Лучковська, С.І. (Часопис Київського університету права, 2009)
В статье анализируется проблема соотношения понятий «валютное ограничение» и «валютный контроль». На основе анализа литературы и законодательства выделяются и исследуются критерии разграничения данных понятий, а также вносятся предложения по усовершенствованию законодательства в этой сфере. The differentiation of the notions «currency restrictions» and «currency control» is analyzed in the article. On the basis of analyzing the literature and legislation the criteria of differentiation of these notions are marked out and searched. In addition some ways of improvements of the legislation in this sphere are proposed.